2020
DOI: 10.1007/s12526-020-01056-w
|View full text |Cite
|
Sign up to set email alerts
|

Atlantic expansion of the African caridean shrimp Lysmata uncicornis Holthuis & Maurin, 1952 (Caridea: Lysmatidae)

Abstract: The present study reports the occurrence of several specimens of the African caridean shrimp Lysmata uncicornis Holthuis and Maurin, 1952 in the NE Atlantic coast (Gulf of Cadiz, Spain and the Algarve, Portugal). Lysmata uncicornis is a poorly studied species that has been originally described from the Atlantic waters of Morocco, where it was first collected inside the port of Casablanca in a rocky bottom at 4-5 m depth. While no scientific publication has previously reported this species outside the waters of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 36 publications
0
11
0
1
Order By: Relevance
“…The expansion of marine species into colder waters is expected in the current scenario of rising seawater temperatures. For example, other African crustaceans have expanded their northern limit of distribution in the northern Atlantic waters (e.g., González-Ortegón et al 2020 ). Since this symbiotic crab has a solitary life inside bivalves (mainly one crab per host, Drake et al 2014 ), it probably has invaded other host bivalves during its geographic expansion to northern latitudes because this diversification of the host species allows it to increase the probability of finding suitable hosts, establishing large populations and decreasing the risk of predation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expansion of marine species into colder waters is expected in the current scenario of rising seawater temperatures. For example, other African crustaceans have expanded their northern limit of distribution in the northern Atlantic waters (e.g., González-Ortegón et al 2020 ). Since this symbiotic crab has a solitary life inside bivalves (mainly one crab per host, Drake et al 2014 ), it probably has invaded other host bivalves during its geographic expansion to northern latitudes because this diversification of the host species allows it to increase the probability of finding suitable hosts, establishing large populations and decreasing the risk of predation.…”
Section: Discussionmentioning
confidence: 99%
“…The spread of nonindigenous species to new ecosystems is becoming increasingly common in many regions of our planet ( Vitousek et al 1997 ). In the current scenario of rising seawater temperatures, marine symbionts exhibit a higher geographical expansion rate to new latitudes ( Drake et al 2014 ): for instance, the African pea crab Afropinnotheres monodi Manning, 1993, as well as other African marine invertebrates, are experiencing a geographical expansion of range in European waters driven by climate change (e.g., González-Ortegón et al 2020 ). Among marine symbionts, the brachyuran crabs of the family Pinnotheridae De Haan, 1833 display a wide diversity of host–guest interactions ( Drake et al 2014 ; Castro 2015 ; Perez-Miguel et al 2019a ); among these, the species of the subfamily Pinnotherinae De Haan, 1833 are characterized by living as ecto or endosymbionts with invertebrates, mainly bivalves ( Castro 2015 ; Palacios Theil et al 2016 ).…”
mentioning
confidence: 99%
“…Creep" by Canning-Clode and Carlton (2017). The number of decapod species that have followed this path in the last decades is significant (e.g., Acantharcus posteli (Forest, 1963) (Barnard, 1947)), and is expected that continues to increase in the future (Encarnação et al, 2019;García-Raso, 1985, 1993García-Raso & Manjón-Cabeza, 1996;González-Ortegón, García-Raso, et al, 2020;Holthuis, 1977;Pozuelo et al, 1976).…”
Section: Biogeographical Implicationsmentioning
confidence: 99%
“…Nauplius, 29: e2021032 introduction The genus Lysmata Risso, 1816, which belongs to the family Lysmatidae Dana, 1852b, is composed of widely distributed species with distinct behavior (social and sexual) and life habits in different marine environments (Bauer, 2000;Rhyne and Lin, 2006;Baeza, 2009;Soledade et al, 2013). Currently, the genus includes 47 species distributed worldwide (Pachelle et al, 2020), with 18 reported in the Atlantic (Chace, 1972;Rhyne and Lin, 2006;Baeza and Anker, 2008;Anker and Cox, 2011;De Grave and Fransen, 2011;Rhyne et al, 2012;Soledade et al, 2013;Gan and Li, 2016;Pachelle et al, 2016;Prakash and Baeza, 2017;Wang and Sha, 2018;De Grave and Anker, 2018;González-Ortegón et al, 2020) and 11 of these on the Brazilian coast in which three of them, Lysmata lipkei Okuno andFiedler, 2010, Lysmata uncicornis Holthuis andMaruin, 1952, andLysmata vittata (Stimpson, 1860), are exotic (Pachelle et al, 2020).…”
Section: Lysmata From Queimada Grande Island Regionmentioning
confidence: 99%
“…The genus Lysmata has species that are highly valuable in the ornamental aquarium industry (Calado et al, 2003;Baeza and Behringer, 2017;Giraldes et al, 2018;González-Ortegón et al, 2020) because they help control pests (anemones of the genus Aiptasia Gosse, 1858) in aquariums, and are visually appealing due to their vivid color patterns (Karplus, 2014;Giraldes et al, 2018). Due to the popularity of Lysmata in the aquarium trade, the demand for them has grown among marketed marine invertebrates (Wabnitz et al, 2003;Calado et al, 2007;Rhyne et al, 2017).…”
Section: Lysmata From Queimada Grande Island Regionmentioning
confidence: 99%